RESPON PETANI KUBIS TERHADAP FLUKTUASI HARGA DAN IKLIM DI KABUPATEN OGAN KOMERING ULU SELATAN” DENGAN KASUS : KUBIS DI KABUPATEN OGAN KOMERING ULU SELATAN YANG DI LAKUKAN PADA TAHUN 2012-2016 (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
This research is done to know the correlation or fluctuation between price and climate to cabbage area in South Ogan Komering Ulu Regency, based on the problem that is how repon of cabbage farmers to price fluctuation and climate in OKUS Regency with the aim of providing information in the management of cabbage farming and provide optimal results. Research conducted in the District Ogan Komering Ulu Selatan election research location done intentionally. The method used is descriptive method, that is the method used for research type using data sekinder. With the object in question is the relationship of price fluctuations and climate with the response of farmers in cultivating cabbage. Type of data taken using secondary data (time series). The results of this study are as follows (1) Cabbage value coefficient value of independent variables in the form of cabbage prices (x1) of -2.628. This means that an increase in cabbage prices of 1 rupiah will decrease the cultivation of cultivation in OKUS Regency of 2,628 ha. With the price of cabbage significant at = 0.05 or a confidence level of 95%. (2) Rainfall coefficient value of independent variables in the form of rainfall (x2) of -2.525. This means that if rainfall rises 1 melimeter then farmers will reduce the area of cultivation in OKUS regency amounted to 2,525 ha. with significant rainfall at = 0.05 or 95% confidence level. From the results of this study can be concluded that the price (x1) and rainfall (x2) significant to cabbage planting area. At α = 0.05 and 95% confidence level.Keywords: Response, Farmers, Price And Climate